Etheno-medicinal plant of Saputara Hill, Dang District, Gujarat. - patel, Rajeshree; varshney, Anjali (International Journal of Scientific Research and Management (IJSRM), 2017)
Some plant used by human community to cure diseases and health related problems from long period oftime are called etheno-medicinal plants. Saputara hill Dang forest is administered by Gujarat stateforest Department (GSFD). The area lies between 20030’ N latitude and 73015’longitude. Saputaraforest (120sq. km) is moist deciduous tropical type with an average rainfall 1200-1500mm. The meantemparature varies from about 80c in winter to about 340c in summer, with 30-80% humidity. Thevegetation of this study area is of purely moist deciduous type with natural plants like Tectona grandis,Dendrocalamus strictus, Terminalia crenulata, T.bellerica, T.arjuna, Carrisa congesta and Accasiacatechu in successive pattern. In conclusion, the medicinal species require special attention to conserveand documentation of their medicinal uses local people.